Synergistic influence of SiC and C3N4 reinforcements on the characteristics of ZrB2-based composites. Issue 1 (2nd January 2021) - Ahmadi, Zohre; Zakeri, Mohammad; Farvizi, Mohammad; Habibi-Yangjeh, Aziz; Asadzadeh-Khaneghah, Soheila; Shahedi Asl, Mehdi
ABSTRACT: In this work, ZrB2 –SiC and novel C3 N4 -doped ZrB2 –SiC composites were manufactured at 1850°C under an external load of 40 MPa for 6 min via spark plasma sintering. The effects of C3 N4 on the mechanical characteristics (flexural strength, Vickers hardness, and fracture toughness) and microstructure of the ZrB2 –SiC-based composites were investigated. By adding 5 wt% g-C3 N4, a fully dense ceramic composite was fabricated, compared to the C3 N4 -free ZrB2 –SiC composite with a relative density of 95%. Removal of ZrO2 and B2 O3 from the surface of ZrB2 particles via chemical reactions with C3 N4, and the in-situ synthesis of ZrC and BN as new phases were studied by XRD and SEM analyses. Indentation fracture toughness, flexural strength, and Vickers hardness improved from 4.5 MPa.m 1/2, 460.2 MPa and 17.4 GPa to 6.1 MPa.m 1/2, 580.2 MPa and 21.2 GPa, respectively, by adding g-C3 N4 to the ZrB2 –SiC ceramic.